Methods and usage of sentiment analysis in the context of the TV industry - Zuell, Beatrice (Array, 2013)
People talk about TV via social media and TV is the number one topic generator. This paper presents the results of testing selected sentiment analysis tools, to research if social media activity in the context of television can be measured and if the tools provide relevant results and consistent information. Selected tools were analysed, to find out if they depict an audience response to the broadcast of a program and which sentiment was shown towards it. As the selected tools use different methodologies and are dependent on restricted access to data sources, the queries delivered different results. Defining adequate queries and identifying the discussions related to a certain program remain the challenge for tools, researchers and audiences.